2022
DOI: 10.1038/s41430-022-01150-1
|View full text |Cite
|
Sign up to set email alerts
|

Red meat consumption and risk factors for type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background and objectives Results from observational studies suggest an association of red meat intake with risk of type 2 diabetes mellitus (T2D). However, results from randomized controlled trials (RCTs) have not clearly supported a mechanistic link between red meat intake and T2D risk factors. Therefore, a systematic review and meta-analysis were conducted on RCTs evaluating the effects of diets containing red meat (beef, pork, lamb, etc.), compared to diets with lower or no red meat, on marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Regarding the number of meals per week, the present study showed no statistically significant association with HbA1c level. This finding is in line with a study done by Sanders, Wilcox & Maki (2022), despite other studies carried out by Sucher et al, (2017) highlighting positive relations. Other observational data also contradicted the study findings, suggesting a positive association (Johnson et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the number of meals per week, the present study showed no statistically significant association with HbA1c level. This finding is in line with a study done by Sanders, Wilcox & Maki (2022), despite other studies carried out by Sucher et al, (2017) highlighting positive relations. Other observational data also contradicted the study findings, suggesting a positive association (Johnson et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological studies carried out in diverse populations indicate that the consumption of meat including red meat is related to an increased risk of developing T2D [ 42 , 43 , 44 , 45 , 46 ]. Conversely, pooled results from a recent systematic review and meta-analysis of 21 RCTs reported no significant impact of red meat intake on various glycaemic indices (i.e., insulin sensitivity, insulin resistance, fasting glucose, fasting insulin, glycated haemoglobin, pancreatic beta-cell function or glucagon-like peptide-1) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased insulin sensitivity can be directly linked to IGT which the World Health Organization (WHO) identifies as a major risk factor for developing T2D [ 48 ]. It has also been argued that increased consumption of SFA may contribute to higher body weight and increased BMI, also significant risk factors for DM [ 31 , 44 , 47 , 48 ]. In the current study, regular meat eaters had a higher body weight, BMI, and waist circumference than all PBD groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the production side, more sustainable agrifood systems can produce more diverse and nutritionally balanced foods, and if poultry (white meat) replaces the red meat that is widely consumed around the world, it will help reduce the risk of many diseases, such as type 2 diabetes, certain cancers, and premature death. 26,27 Many dietary guidelines recommend reducing red meat intake and increasing healthy alternatives, such as white meat, to compensate for potential key nutrients. 28 However, changes in the dietary structure of Chinese residents have also exacerbated environmental problems.…”
Section: Discussionmentioning
confidence: 99%